-8x-62=64-2x

Simple and best practice solution for -8x-62=64-2x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -8x-62=64-2x equation:


Simplifying
-8x + -62 = 64 + -2x

Reorder the terms:
-62 + -8x = 64 + -2x

Solving
-62 + -8x = 64 + -2x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '2x' to each side of the equation.
-62 + -8x + 2x = 64 + -2x + 2x

Combine like terms: -8x + 2x = -6x
-62 + -6x = 64 + -2x + 2x

Combine like terms: -2x + 2x = 0
-62 + -6x = 64 + 0
-62 + -6x = 64

Add '62' to each side of the equation.
-62 + 62 + -6x = 64 + 62

Combine like terms: -62 + 62 = 0
0 + -6x = 64 + 62
-6x = 64 + 62

Combine like terms: 64 + 62 = 126
-6x = 126

Divide each side by '-6'.
x = -21

Simplifying
x = -21

See similar equations:

| x+3x-2=78 | | 128=96t-16t^2 | | 4y+8=4y-9 | | -8=9v-5+32 | | s-3=5-2 | | 10=5(x+3) | | 3x+18=x+32 | | 5w+8-w=7w-2(w-4) | | 1-3=5-1 | | 7m-3=9m+6-m | | -85+3x=83-9x | | (5x-3)+(n+9)=24 | | X^3+13x^2=0 | | 6y+4=6y-9 | | 16(z+3)=4(z-9) | | (2x-4)(x+3)= | | 2a-4b=58 | | -a+5=5a+5 | | 3x-7=-3 | | F(5)=20x+11 | | 4x^3+8x^2+3x+6=0 | | q-rb=15a | | 2x+12i=3y+2yi | | 12p=p+24+p | | 18x^2+45x+15=-10 | | 2w+9=-3 | | 2m+5=m+4 | | sin(10x)*cos(5x)=0 | | 3(x^2-10)-3x=6(x^2-2x) | | 4(y+4)+3=39 | | (8y+13)(5y+24)=0 | | (4x+4)(8x+10)=0 |

Equations solver categories